Using the R Language to Manage and Show Statistical Information in the Cloud - Fonseca i Casas, Pau; Tormos, Raül (Technologies (Basel), 2018)
We present a methodology to enable users to interact with the statistical information (survey data) of a public opinion institute which is stored in Cloud infrastructure. Mainly using R, this approach was developed following the open-data philosophy. Also, as we used R, the implementation is mainly based on open-source software. R has several advantages from the point of view of data management and acquisition, as it is becoming a common framework that can be used to structure the processes involved in any statistical operation. It further simplifies the access to data and enables the use of all the power of R in Cloud infrastructure. This methodology was applied successfully to develop a tool to manage the data of the Centre d’Estudis d’Opinió, but it can be applied to other institutions to enable open access to their data. The infrastructure was also deployed to Cloud infrastructure to assure its scalability and 24/7 access.